2021
DOI: 10.1177/0961203320984845
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and prevalence of systemic lupus erythematosus among Korean women in childbearing years: A nationwide population-based study

Abstract: Background Most women with systemic lupus erythematosus (SLE) are diagnosed with the disease in their reproductive years, but the incidence and prevalence of SLE among women of childbearing age have not been studied. The objective of this study was to estimate the incidence and prevalence of SLE among the Korean women of childbearing age. Methods Women aged 20 to 44 years with SLE were identified from National Health Insurance Service – National Health Information Database (2009-2016), which contain health inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
3
9
0
Order By: Relevance
“…Same as previous study, the risk and burden of SLE are high among women during their childbearing years. 25 In line with what we have found, low income would reduce the quality of life of patients, as reported in the previous study. 26 McCormick et al found high financial stress was an important predictor of new depression in SLE patients after controlling for disease factors and other measures.…”
Section: Discussionsupporting
confidence: 90%
“…Same as previous study, the risk and burden of SLE are high among women during their childbearing years. 25 In line with what we have found, low income would reduce the quality of life of patients, as reported in the previous study. 26 McCormick et al found high financial stress was an important predictor of new depression in SLE patients after controlling for disease factors and other measures.…”
Section: Discussionsupporting
confidence: 90%
“…We have recently reported the incidence and prevalence of systemic lupus erythematosus (SLE) among Korean women of childbearing age using the same NHIS-NHID database [ 37 ]. Although we found that risks of SLE and SPRA are high in women during their childbearing years and this population bears a significant burden of both diseases, a noteworthy difference was observed between the epidemiology of SPRA and SLE.…”
Section: Discussionmentioning
confidence: 99%
“… 4 Furthermore, the incidence and prevalence rates peak in women during their childbearing years. 3 RA is also approximately 2 times more prevalent among women than among men, 5 and the female-to-male ratio is 3.7:1 before 30 years of age but decreases to 1:1 after the 6 th decade of life. 6 AS occurs more frequently in men, but the proportion of women with a new diagnosis of AS has been increasing, especially in women of childbearing age.…”
Section: Introductionmentioning
confidence: 99%
“…Rheumatic diseases (RDs) such as rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), and ankylosing spondylitis (AS) occur often in women of childbearing age. 1 2 3 In SLE, the male-to-female ratio of disease incidence is 1:9, and this ratio increases up to 1:15 in individuals of reproductive age. 4 Furthermore, the incidence and prevalence rates peak in women during their childbearing years.…”
Section: Introductionmentioning
confidence: 99%